A beautiful new yellow salamander, genus Bolitoglossa (Caudata: Plethodontidae), from the northeastern slopes of the Cordillera de Talamanca, Costa Rica - Kubicki, Brian; Arias, Erick (Zootaxa, 2016)
A new yellow salamander belonging to the genus Bolitoglossa, subgenus Eladinea, is described from a premontane rainforest in the vicinity of Moravia de Chirripó, on the northeastern slopes of the Cordillera de Talamanca in Costa Rica at an elevation of ca. 1300 m. This new taxon is distinguished from its congeners by its chromatic and morphological characteristics, and by differentiation in DNA sequences of the mitochondrial 16S rRNA and cytochrome b genes.